Dynamics of land occupation in the municipality of Novo Repartimento, Pará, Brazil - Souza, Manuela Braga de; Mesquita, Ana Luísa da Costa; Silva Júnior, Orleno Marques da; Cardoso, Pedro Monteiro; Ruivo, Maria de Lourdes Pinheiro; Paiva, Paula Fernanda Pinheiro Ribeiro (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The municipality of Novo Repartimento, Pará, went through a disorderly process of urban expansion, due to the intensification of agricultural activities, which triggered the occupation of environmentally fragile areas. This occupation accentuated negative impacts caused by deforestation by changing landscapes. Thus, the objective of the study was to analyze and evaluate the evolution of land use and occupation with emphasis on deforested areas. The procedures consisted of the elaboration and crossing of thematic maps in order to establish hierarchical classes of the variable deforestation; multitemporal analysis of the evolution of the classes of use and occupation between two distinct periods: 2000 and 2019, with the help of geotechnologies. We used cartographic data available in the database of the Brazilian Institute of Geography and Statistics, the MapBiomas Project and Google Earth Engine. The results demonstrated the importance of the use of geotechnologies for the sustainable planning of land occupation in which, it is observed that deforestation in the municipality is increasing, and within the main variables and correlations, stands out the agricultural and timber sector.